Reusa, recicla, recapacita - Estudio Ayerra & Bardavid (2009)
Magma
Keywords: AYERRA, FABIO; BARDAVID, GUSTAVO; URUGUAY; MONTEVIDEO; ARQUITECTURA COMERCIAL; LOCALES COMERCIALES; SHOPPING CENTERS; CONSTRUCCION; CERRAMIENTOS; PLASTICOS; RECICLAJE